International Academic Programs and Models in Anti-Corruption Education and Their Implementation at UNWE - Spassov, Svetoslav (Research Papers, 2022)
The аnti-corruption education is relatively a new aspect of the educational and academic programs of the Bulgarian universities. The current study aims to analyze the world’s leading academic models and best practices in preventing corruption, developed by the United Nations Organization on Drugs and Crime (UNODC), including the UNODC Anti-Corruption Academic Program (ACAD), the Anti-Corruption Course, the Education for Justice Initiative (E4J), the International Anti-Corruption Academy (IACA), as well as by the world’s leading universities, state institutions and non-governmental organizations. The article analyzes the implementation of the Master’s program in anti-corruption at UNWE, supported by UNODC.